Analysis of the Influence of Government Expenditure in the Fields of Education, Social Protection, Public Services, Infrastructure, Community Empowerment, Investment, and HDI on Economic Growth in the 3T Regions (Underdeveloped, Frontier, and Outermost) of Indonesia - Wardani Pulungan, Rafika; Afifuddin Sembiring, Sya’ad; Rahmanta, Rahmanta (International Journal of Social Science, Education, Communication and Economics, 2024)
This study examines the impact of government expenditure in education, social protection, public services, infrastructure, community empowerment, investment, and the Human Development Index (HDI) on economic growth in Indonesia’s Disadvantaged, Frontier, and Outermost (3T) regions before and after the COVID-19 pandemic. Employing a quantitative approach, this research analyzes panel data from 62 regencies categorized as 3T regions from 2017 to 2022. The study uses panel data regression analysis to evaluate the influence of these expenditures on economic outcomes. Findings indicate that government spending in the education sector consistently had a positive effect on economic growth before and after the pandemic. Conversely, expenditure in social protection and HDI shifted from having a positive to a negative impact post-pandemic. Meanwhile, investments in public services, infrastructure, and overall investment, which previously had a negative impact, showed a positive influence in the post-pandemic period. Overall, government spending across all sectors had a simultaneous and significant positive effect on economic growth in the 3T regions. These results underscore the need for evidence-based policy interventions to enhance the effectiveness of government spending in promoting equitable economic growth in underdeveloped areas.